Analisis NilaiiReligius dalamiSyair PeuayoniAneuk DiiKecamatan Setia Bakti KabupateniAceh Jaya - Moni Alafanta; Armia Armia; Muhammad Iqbal (JIM Pendididikan Bahasa dan Sastra Indonesia, 2019)
This research is entitled "Analysis of Religious Values in Poetry Peuayôn Aneuk in Setia Bakti Subdistrict, Aceh Jaya Regency. The formulation of the problem is (1) what religious values are contained in the poetry of Peuayôn Aneuk, (2) what religious values are dominant in the poetry of Peuayôn Aneuk. The purposeoof this study isoto describeotheoreligious values containedoin the poetry of Peuayôn Aneuk in Setia Bakti District, Aceh Jaya Regency. The research method used is descriptive qualitative method. The research data collection technique was obtained through the skillful engaging listening technique and note-taking technique. Techniques for analyzing the data used in this study were (1) data collection, (2) reading the verses that will be analyzed repeatedly to achieve a level of understanding of the elements of religious values contained in Peuayôn Aneuk's poetry, (3) describing the content of verse one one by one, namely the description of the religious values contained in these verses, (4) clarifying the lines of poetry that contain religious values in the poetry of Peuayôn Aneuk, (5) drawing conclusions. The religious values contained in the poetry of Peuayôn Aneuk are aspects of religious values that relate to God, the social environment, humans and humans with oneself. Poetry Peuayôn Aneuk in Setia Bakti sub-district is widely used to put children to sleep and the content of Syair Peuayôn Aneuk tells about various aspects of life related to religiousivalues, namelyi(1) human relationsiwith God,i(2) human relationsawith the social environment, (3) human relations with humans, (4) human relationships with oneself.